SCREENING FOR PULMONARY TUBERCULOSIS USING CHEST X-RAY WITH COMPUTER-AIDED DETECTION SYSTEMS: A LITERATURE REVIEW (Vietnam Journal of Community Medicine, 2022)
Objective: To review the literature on pulmonary TB screening using automatic X-ray film readingsystems.Subjects and methods: 13 publications from 2 databases MEDLINE and Cochrance in the periodfrom January 2010 to December 2021 were analyzed.Results: Our study has shown that there are currently 12 automatic chest X-ray reading systems thathave been applied in screening for pulmonary tuberculosis. The sensitivities of the systems rangedfrom 0.70 to 0.95 with specificities of 0.42 to 0.99, respectively. Of these, there are 3 systems thatachieve the sensitivity and specificity recommended by WHO for a TB screening tool (sensitivity>=90% and specificity >=70%) namely: qXR, CAD4TB and INSIGHT CXR.Conclusion: Our study has highlighted the overview and value of some AI software applications inreading chest X-ray automatically supporting the diagnosis of pulmonary tuberculosis.
Keywords: TB screening, Pulmonary tuberculosis, Chest X-ray, Computer-aided detection.